An ionic liquid supported on magnetite nanoparticles as an efficient heterogeneous catalyst for the synthesis of alkyl thiocyanates in water. (4th May 2021) - Fallah-Mehrjardi, Mehdi; Sayyahi, Soheil
ABSTRACT: The present study describes a convenient method to synthesize alkyl thiocyanates from alkyl halides with the use of a novel nanomagnetic-supported organocatalyst (MNP@PEG-ImCl). The new supported ionic liquid is fully characterized by field-emission scanning electron microscopy (FESEM), Fourier-transform infrared (FT-IR), energy dispersive X-ray analysis (EDAX), X-ray powder diffraction (XRD), transmission electron microscopy (TEM), vibrating sample magnetometry (VSM) as well as thermogravimetric analysis (TGA) techniques. It is noteworthy that we observed easy separation of the catalyst from the reaction mixture by a simple magnetic decantation and its reutilization many times without any appreciable loss of activities. GRAPHICAL ABSTRACT: